Scandix pecten-veneris L. (Apiaceae) in the Małopolska Upland (S Poland) – regional changes in the distribution and population resources of declining weed species - Łazarski, Grzegorz (Biodiversity: Research and Conservation, 2016)
The paper presents results of the inventory of localities of Scandix pecten-veneris L. in the Małopolska Upland conducted after 2000. The existing population resources were estimated and current distribution of the species in the Małopolska Upland and Poland was showed. Some threats to this species as well as conservation prospects were discussed.